2018
DOI: 10.1080/08856257.2018.1501965
|View full text |Cite
|
Sign up to set email alerts
|

School belonging among young adolescents with SEMH and MLD: the link with their social relations and school inclusivity

Abstract: Despite the considerable institutional changes schools have made to accommodate the individual needs of pupils with special educational needs and disabilities (SEND), as underpinned by key principles of inclusion, there is still international concern about the mainstream experiences pupils with SEND have in school settings. This study helps us gain a clearer understanding of the schooling experiences of pupils with social emotional and mental health (SEMH) difficulties and moderate learning difficulties (MLD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…As this study has indicated, pupils with SEMH were the ones who expressed the greatest dissatisfaction with school when compared to pupils with MLD and their typical counterparts. It can thus be speculated that the needs of pupils with SEMH are less satisfied within mainstream settings as compared to the needs of pupils with MLD (Dimitrellou and Hurry, ; Murray and Greenberg, ). Yet, despite their expressed differences, all pupils, irrespective of their type of need, voiced quite similar views on what makes a positive school experience for them.…”
Section: Discussionmentioning
confidence: 99%
“…As this study has indicated, pupils with SEMH were the ones who expressed the greatest dissatisfaction with school when compared to pupils with MLD and their typical counterparts. It can thus be speculated that the needs of pupils with SEMH are less satisfied within mainstream settings as compared to the needs of pupils with MLD (Dimitrellou and Hurry, ; Murray and Greenberg, ). Yet, despite their expressed differences, all pupils, irrespective of their type of need, voiced quite similar views on what makes a positive school experience for them.…”
Section: Discussionmentioning
confidence: 99%
“…Friendships are, however, crucial for the well‐being, self‐worth and social‐emotional development of students (e.g., Mitic et al., 2021; Maunder et al., 2019; Kidger et al., 2012). In this context, it has been highlighted, that students with behaviour difficulties and hyperactivity have less sense of school belonging (see e.g., Dimitrellou & Hurry, 2019). In addition, research indicates that this group of students has more peer difficulties (see e.g., Gardener et al., 2015) and difficulties maintaining friendships (Marton et al., 2015) compared to their peers without such symptoms.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Theorists suggested that the quality of social relationships contributes directly and positively to developing students' sense of school belonging. However, several types of relationships can be considered, including friendships, dyadic relationships, teacher/students' relations, peer relations, social processes present in class, or peer acceptance (Dimitrellou & Hurry, 2019;Juvonen, 2006;Ibrahim and El Zaatari, 2020). Within these different types of relationships, the quality of social bonds must be present, and acceptance must prevail over social isolation.…”
Section: The Relational Climatementioning
confidence: 99%
“…As an element negatively influencing school belonging, the concept of social isolation refers precisely to the need for students to interact frequently with their peers (Dimitrellou & Hurry, 2019;London and Ingram, 2018;Wehlage et al, 1989). However, in order to foster quality social relations, teachers obviously have a role to play.…”
Section: The Relational Climatementioning
confidence: 99%